Comparison of short-term outcomes of open appendectomy and laparoscopic appendectomy in patients with acute appendicitis - Warda Iram; Humayun Amjad; Bria Qaiser (Medical Journal of South Punjab, 2025)
Objective: To compare laparoscopic appendectomy and Open appendectomy in terms of short-term outcomes in patients with acute appendicitis. Methodology: Study was commenced at Department of Surgery at Ibn-e-Siena Hospital, Multan, as a randomized controlled trial over six months following the approval of the synopsis. A total of 60 patients, with 30 in each group, were included in the study using non-probability consecutive sampling. Patients were followed up weekly in the outpatient department for 30 days postoperatively. The occurrence of surgical site infection and seroma formation was assessed. Results: Mean duration of surgery of LA was significantly higher than OA, 63.13±3.28 minutes and 46.90±2.23 minutes, respectively (p<0.001). Mean duration of hospital stay of OA was significantly higher than OA, 3.03±0.92 days and 1.90±0.61 days, respectively (p<0.001). Surgical site infection was significantly higher in OA 12 (40.0%) than LA 3 (10.0%). (p=0.007). Whereas, seroma formation was observed in 6.7% OA and 3.3% in LA (p=0.129). Conclusion: Laparoscopic appendectomy offers advantages over open appendectomy in terms of reduced postoperative pain, shorter hospital stays, and lower wound infection rates, making it a preferred approach where feasible. However, the longer operative time and slightly higher risk of intra-abdominal abscess formation should be considered when selecting the surgical technique.